2000
DOI: 10.1107/s0108768100000252
|View full text |Cite
|
Sign up to set email alerts
|

Structures of [Pd(NH3)2 X 2] and its chemical transformation in the solid state

Abstract: Crystal structures of [Pd(NH3)2X2] complexes, where X = Br or I, diamminediiodo-/-dibromopalladium(II), have been studied by X-ray powder diffraction. The series consists of five complexes: cis-[Pd(NH3)2Br2] (I) [a = 13.3202 (7), b = 12.7223 (6), c = 7.05854 (3) A, Z = 8, space group Pbca], trans-[Pd(NH3)2Br2] (II) [a = 6.7854 (3), b = 7.1057 (3), c = 6.6241 (2) A, alpha = 103.221 (3), beta = 102.514 (2), gamma = 100.386 (3) degrees, Z = 2, space group P1], beta-trans-[Pd(NH3)2Br2] (III) [a = 8.4315 (3), b = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…All peaks originating from [PtCl(NCN-OH)] were absent. Exposure of a sample of the adduct to air completely reversed the process of this selective inclusion of SO 2 into these arylplatinum structures which involved successive making and breaking of Pt-SO 2 -Cl interactions (Table 4 - 39). Because the process of SO 2 gas absorption/desorption is fully reversible over many 'on/off' cycles without any material deterioration, and is accompanied by a distinct color change the authors have proposed its application as a 'molecular switch' for SO 2 sensing.…”
Section: Solid-gas Reactionsmentioning
confidence: 98%
See 2 more Smart Citations
“…All peaks originating from [PtCl(NCN-OH)] were absent. Exposure of a sample of the adduct to air completely reversed the process of this selective inclusion of SO 2 into these arylplatinum structures which involved successive making and breaking of Pt-SO 2 -Cl interactions (Table 4 - 39). Because the process of SO 2 gas absorption/desorption is fully reversible over many 'on/off' cycles without any material deterioration, and is accompanied by a distinct color change the authors have proposed its application as a 'molecular switch' for SO 2 sensing.…”
Section: Solid-gas Reactionsmentioning
confidence: 98%
“…The authors concluded that the cis ! trans transformation was not just a transition between the phases but occurred through the breaking of Pd-N or Pd-X bonds to finally yield the thermodynamic products (Table 3 -32) [39].…”
Section: Cis-trans Isomerization Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the chemical composition of two materials is the same, the crystal structure may be markedly different. In XRD, a wide peak means low crystallinity, and a narrow peak means high crystallinity . In this study, P400 and P1200 showed the hydroxyapatite peaks and P400 showed a wider peak, indicating a lower crystallinity than P1200.…”
Section: Discussionmentioning
confidence: 50%
“…In this specific case the reaction proceeds from the cis to the trans isomer in a process that entails the ''breaking of PdϪX and PdϪN bonds''. [29] Numerous sixcoordinate Cr and Co compounds have also been studied. [30] It appears that the presence of water assists the cis/trans isomerization reaction of Co complexes, with dehydration playing a key role.…”
Section: Inorganic Moleculesmentioning
confidence: 99%